Determinación de los costos de producción y rentabilidad del cultivo del plátano dominico-hartón (Musa aab) vs cultivo del plátano barraganete (Musa sp) en la parroquia el Vergel, Cantón Valencia. - Alvarez Reyes, Yomira Maribel (2018)
This research entitled "Study of the yield and profitability of the cultivation of the plantain-hartón banana (musa aab) vs cultivation of the banana plantain (musa sp) in the parish of El Vergel cantón Valencia has as objective to know more about these two varieties of plantain since they are being produced in large quantities in our country. The methodology applied in this research collaborated through the questionnaire to obtain essential information to know the costs of production and cost of sales of the plantain that are generated in El Vergel. In the Results it was obtained that the producers in the El Vergel area are engaged in two plantation crops of two varieties of plantain but with preferences to the plantain Dominico Hartón since they have safe contracts throughout the year, besides the weight is ideal for the boxes of export The yield obtained weekly on one hectare is favorable for farmers since it was concluded that acceptable quantities are obtained in boxes obtaining a stable profitability to cover expenses and needs. Keywords: cost of production, cost of sale, Dominican-hartòn